Successful retrieval of tip-embedded inferior vena cava filter using a modified forceps technique: case report - Yang Liu; Junlong Ma; Qiqi Wang; Wei Zeng; Chunshui He (Thrombosis Journal, 2024)
Abstract Background The retrieval of inferior vena cava (IVC) filter is essential for preventing complications associated with the device. Advanced techniques have been developed to improve the success rate of retrieving tip-embedded filters. The forceps technique is frequently used to address this issue. Case presentation We present a case study of two patients who underwent a successful tip-embedded IVC filter retrieval using a modified forceps technique, which has not been previously reported. This technique involves using a wire loop under the filter tip and a forceps to grasp the filter shoulder. By pulling the wire loop and pushing the forceps in counterforce, the filter tip is straightened and aligned with the vascular sheath. The vascular sheath can then dissect the filter tip out from the caval wall and get inside the sheath to complete the retrieval. Conclusions The modified forceps technique we present here offers a new solution for the complex retrieval of IVC filters.